A Paradigm Change: From Performance Monitoring to Performance Analysis - DeRose, Luiz; Poxon, Heidi (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2009)
The purpose of an application performance tool is to help users identify whether or not their application are running efficiently on the computing resources available. However, the scale of current and future high end systems, as well as increasing system software and architecture complexity, brings a new set of challenges for performance tuning. To achieve high performance on peta-scale systems, users need a new infrastructure for performance measurement that can automate the process of performance analysis. In order to address these issues, we designed an automatic performance analysis framework, which contains innovative techniques that use a knowledge base and set of performance models. In this paper we outline the key aspects of this design and present the features from this design that have been implemented in the Cray Performance Analysis Toolset.